2020
DOI: 10.3389/fmicb.2020.00420
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Alcohol Induced Gastric Ulcers Through the Administration of Lactobacillus plantarum APSulloc 331261 Isolated From Green Tea

Abstract: Gastric inflammation is an indication of gastric ulcers and possible other underlying gastric malignancies. Epidemiological studies have revealed that several Asian countries, including South Korea, suffer from a high incidence of gastric diseases derived from high levels of stress, alcoholic consumption, pyloric infection and usage of non-steroidal anti-inflammatory drugs (NSAIDs). Clinical treatments of gastric ulcers are generally limited to proton pump inhibitors that neutralize the stomach acid, and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…In a mouse model that combined ethanol and H. pylori administration, Park et al treated the animals with green tea-derived L. plantarum , concluding that these probiotics decreased inflammation and improved gastric ulcers, possibly by restoring healthy gut microbiota [ 119 ]. In another study by the same group, mice were fed L. plantarum before H. pylori infection.…”
Section: Management Of Helicobacter Pylori Infectionmentioning
confidence: 99%
“…In a mouse model that combined ethanol and H. pylori administration, Park et al treated the animals with green tea-derived L. plantarum , concluding that these probiotics decreased inflammation and improved gastric ulcers, possibly by restoring healthy gut microbiota [ 119 ]. In another study by the same group, mice were fed L. plantarum before H. pylori infection.…”
Section: Management Of Helicobacter Pylori Infectionmentioning
confidence: 99%
“…Caspase 3 is the key executor protein for the caspases cascade reaction of apoptosis, interacting with caspase-8 and caspase-9 [9,10]. Numerous in vivo studies have reported that many genera of probiotic Lactobacilli had protective effects on the gastric mucosa; the underlying mechanisms, however, remain to be fully elucidated [11][12][13][14][15][16]. Lactate is a major metabolite of Lactobacilli that has been widely used as a food additive for human [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it markedly increased the abundance of various intestinal bene cial bacteria such as Bi dobacterium spp. and Clostridium butyricum [33]. Furthermore, L. plantarum APsulloc 331261-derived extracellular vesicles exerted anti-in ammatory effects on human skin by inducing macrophage polarisation [34].…”
Section: Introductionmentioning
confidence: 99%
“…L. plantarum strains APsulloc 331261 and 331266 isolated from green tea (Camellia sinensis) have been sequenced and annotated using whole-genome sequence analysis, and their safety and bene ts have also been described [32]. L. plantarum APsulloc 331261 alleviated gastric in ammation in an alcoholinduced gastric ulcer murine model [33]. Moreover, it markedly increased the abundance of various intestinal bene cial bacteria such as Bi dobacterium spp.…”
Section: Introductionmentioning
confidence: 99%